Le bas-Oyapock : un fleuve, une frontière, des frontières ? - Sylvie Letniowska-Swiat; Valérie Morel (Confins)
The Lower Oyapock watershed is located in a border area. It is an original space, structurally a margin, which over time has developed logics of functioning in a pool of life atypical compared to the rest of the territories of French Guiana and Amapá. The antagonistic and complementary spatial functions of this border zone were set up in reaction to the degree of integration of this more or less thick border of national spaces and have over time erected it in transnational space. Today, the presence of the bridge and especially its recent opening have re-functionalized the border position of the river. Object of link between France and Brazil, the international bridge of the Oyapock highlights this space of borders but currently has little or no concrete action on the "demarginalization" of the watershed. With the strengthening of the controls that accompany the establishment of the crossing point by the bridge, the traditional functioning of the living area has been disrupted, revealing a border long erased and denied by the social, economic, cultural and health practices of populations. Today, lower-Oyapock is renewing its margin operation, particularly in its thickness and in the territorial dynamics it generates.